Artificial intelligence approach for fire monitoring and warning system design - Kiethson, Branden Adems; Mohd Khairuddin, Ismail; Anwar P. P., Abdul Majeed; Mohd Razman, Mohd Azraai; Abdullah, Muhammad Amirul; Mohd Isa, Wan Hasbullah (Penerbit UMP, 2022)
Fire alarm system consist of several type of sensors that works togeher in order to detect a fire breakouts. But the systems itself consist of errors especially detecting smoke which sometimes could not lead to a potential fire breakouts instead causing a false alarm. Moreover, vision cameras are expensive to be installed and it takes a lot amount of money for maintenance alone. This causes many household does not equip with such devices making fire breakouts to be inevitable. In this research, the aim of this is to create a system that is cheap and could detect a potential fire before it could even happen by applying Fuzzy logic technique. By adding an Artificial Intelligence in a fire monitoring and warning systems, This could reduce error and predict the right event that could lead to a fire breakouts. With this, many household especially in Malaysia could have the safety to overcome this